Women’s attitude in Poland and Belarus toward the issue of induced abortion - Jaszkiewicz, Anna; Zalewski, Jerzy; Surdyka, Justyna; Heimrath, Jerzy (Polish Journal of Public Health, 2013)
Introduction. In most countries, abortion is allowed to save woman’s physical and mental health. In Poland, women have no right to abortion on demand; the procedure is illegal and punishable by imprisonment up to 3 years. In the neighbouring country of Belarus, induced abortion on demand is legal through the 12th week of pregnancy, while for social reasons and on demand, through the 22nd week of pregnancy, in governmental hospitals only. Abortion deserves the name of one of the most serious contemporary ethical dilemmas and constitutes one of the most difficult problems in medical ethics. Performing abortion continues to be opposed by many individuals and communities. Aim. The study of the attitude of women in Poland toward the problem of induced abortion and the comparison of their attitude with that of women in Belarus.Material and methods. The method used to conduct this study was a diagnostic survey using a questionnaire designed for the purpose of this work. The study was conducted among women in Poland and Belarus. The group surveyed was comprised primarily of young women of reproductive age, with the desire to conceive, have families or plan to have families. Two hundred surveys, properly filled out, 100 from Poland and 100 from Belarus, qualified for the analysis.Results. The comparative analysis of the responses of the women surveyed in Poland and Belarus demonstrated that in both countries attitudes toward the problem of induced abortion and women’s opinions on the use of induced abortion are still divided.Conclusions. Women of Belarus are more supportive of abortion and they consider it less shocking and more common than women from Poland.